Antibacterial effects of new endodontic materials based on calcium silicates - Trišić, Dijana; Ćetenović, Bojana; Zdravković, Nemanja; Marković, Tatjana; Dojčinović, Biljana; Jokanović, Vukoman; Marković, Dejan (Vojnosanitetski pregled, 2021)
Background/Aim. The main task of endodontic treatment is to eliminate pathologically altered tissue, to disinfect root canal space and to obtain its three-dimensional hermetic obturation. The main purpose of this study was to evaluate antimicrobial activity of new endodontic nano-structured highly active calcium silicates based materials albo-mineral plyoxide carbonate aggregate (ALBO-MPCA) and calcium silicates (CS) in comparison to mineral trioxide aggregate (MTA+) and UltraCal XS (CH). Methods. The antimicrobial activity of materials was tested against Staphylococcus aureus (ATCC 25923) and Enterococcus faecalis (ATCC 14506) strains, and following clinical isolates: Rothia dentocariosa, Enterococcus faecalis, Staphylococcus aureus, Streptococcus anginosus and Streptococcus vestibularis using a double layer agar diffusion test. The pH measurements were performed using the pH meter. Total amount of released ions was determined by inductively coupled plasma optical emission spectrometry (ICP-OES). Results. All tested materials showed the best antibacterial potential after 1 h of incubation. After 3h and 24h of the incubation period, the antibacterial potential of all tested materials were similar. The Agar diffusion test showed that ALBO-MPCA, CS and MTA+ had similar inhibition zones (p > 0.05), except in the activity against Staphylococcus aureus where ALBO-MPCA showed better antimicrobial properties than MTA+ in 3h and 24h of the incubation period (p
Keywords: dental pulp diseases; root canal preparation; calcium silicate; calcium hydroxide; anti-infective agents.